Pathogenic Leptospira Secreted Proteases Target the Membrane Attack Complex: A Potential Role for Thermolysin in Complement Inhibition - Amamura, Thais A.; Fraga, Tatiana R.; Vasconcellos, Sílvio A.; Barbosa, Angela S.; Isaac, Lourdes (Frontiers in Microbiology, 2017)
Leptospirosis is a zoonosis caused by spirochetes from the genus Leptospira. This disease is common in tropical and subtropical areas, constituting a serious public health problem. Pathogenic Leptospira have the ability to escape the human Complement System, being able to survive when in contact with normal human serum. In a previous study, our group demonstrated that supernatants of pathogenic Leptospira (SPL) inhibit the three activation pathways of the Complement System. This inhibition can be directly correlated with the activity of secreted proteases, which cleave the Complement molecules C3, Factor B (Alternative Pathway), C4 and C2 (Classical and Lectin Pathways). In this work, we analyze the activity of the leptospiral proteases on the components of Terminal Pathway of Complement, called the Membrane Attack Complex (MAC). We observed that proteases present in SPL from different Leptospira strains were able to cleave the purified proteins C5, C6, C7, C8 and C9, while culture supernatant from nonpathogenic Leptospira strains (SNPL) had no significant proteolytic activity on these substrates. The cleavages occurred in a time-dependent and specificity manner. No cleavage was observed when we used whole serum as a source of C5-C9 proteins, probably because of the abundant presence of plasma protease inhibitors such as α2-macroglobulin. Complement protein cleavage by SPL was inhibited by 1,10-phenanthroline, indicating the involvement of metalloproteases. Furthermore, 1,10-phenanthroline- treated normal human serum diminished pathogenic leptospira survival. We also analyzed the proteolytic activity of thermolysin (LIC13322) a metalloprotease expressed exclusively by pathogenic Leptospira strains. Recombinant thermolysin was capable of cleaving the component C6, either purified or as part of the SC5b-9 complex. Furthermore, we found that the MAC proteins C6-C9 interact with thermolysin, indicating that this metalloprotease may have an additional inhibitory effect on these molecules by direct interactions. Finally, a functional assay demonstrated that thermolysin was able to inhibit MAC-dependent erythrocytes lysis. We conclude that proteases secreted exclusively by pathogenic Leptospira strains are capable of degrading several Complement effector molecules, representing potential targets for the development of new therapies and prophylactic approaches in leptospirosis.